2021
DOI: 10.1177/08862605211042815
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Considerations of Remorse and Responsibility Among Youth Who Sexually Offend

Abstract: When a youth sexually offends, most of the reactions and repercussions that follow are understandably negative. However, there is limited research about mixed reactions involving remorse and responsibility on the part of the adolescent who offended and their relatives. Based on qualitative interviews with 16 caregivers among 10 families in Canada, this article presents the parents’ perspectives on the various processes, benefits, challenges, and outcomes related to expressions of remorse and experiences of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…With regard to supports, caregivers shared that they faced considerable barriers in accessing help for their families and that the available interventions were unhelpful and unnecessary as they often involved the use of child welfare and/or youth justice systems. The Consortium's findings are consistent with other studies based on caregivers' concerns regarding AFCCA (Clarke et al, 2017;Condry et al, 2020;Holt et al, 2011;Selwyn and Meakings, 2016;Selwyn et al, 2014), as well as other research on parental perspectives on other harm-generating behaviours exhibited by children and youth (Gervais and Johnston, 2022;Gervais and Romano, 2019;Gervais and Romano, 2018;Hackett et al, 2014). Yet, despite the growing literature on AFCCA that examines relatives' views, as well as the complex set of factors that place young people at risk for this behaviour, most of this research has been conducted outside of Canada, and the literature does not appear to have approached the issue of AFCCA specifically from a child rights' perspective.…”
Section: Introductionsupporting
confidence: 87%
“…With regard to supports, caregivers shared that they faced considerable barriers in accessing help for their families and that the available interventions were unhelpful and unnecessary as they often involved the use of child welfare and/or youth justice systems. The Consortium's findings are consistent with other studies based on caregivers' concerns regarding AFCCA (Clarke et al, 2017;Condry et al, 2020;Holt et al, 2011;Selwyn and Meakings, 2016;Selwyn et al, 2014), as well as other research on parental perspectives on other harm-generating behaviours exhibited by children and youth (Gervais and Johnston, 2022;Gervais and Romano, 2019;Gervais and Romano, 2018;Hackett et al, 2014). Yet, despite the growing literature on AFCCA that examines relatives' views, as well as the complex set of factors that place young people at risk for this behaviour, most of this research has been conducted outside of Canada, and the literature does not appear to have approached the issue of AFCCA specifically from a child rights' perspective.…”
Section: Introductionsupporting
confidence: 87%
“…12. All parents reported that their offending son faced cognitive and/or mental health challenges; however, we did not thoroughly examine their implications in this article; we do so elsewhere (Gervais & Johnston, 2021). …”
mentioning
confidence: 99%